2017
DOI: 10.1002/jbm.b.33869
|View full text |Cite
|
Sign up to set email alerts
|

The effect of Mg–Ca–Sr alloy degradation products on human mesenchymal stem cells

Abstract: Biodegradable Mg alloys have the potential to replace currently used metallic medical implant devices, likely eliminating toxicity concerns and the need for secondary surgeries, while also providing a potentially stimulating environment for tissue growth. A recently developed Mg–Ca–Sr alloy possesses advantageous characteristics over other Mg alloys, having a good combination of strength and degradation behavior, while also displaying potentially osteogenic properties. To better understand the effect of alloy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 31 publications
0
6
0
1
Order By: Relevance
“…Contrasting results were reported in the literature about the Mg effect on bMSC fate. Some studies on the effect of Mg alloy degradation show cell mineralization induction [70,71], while most of the studies demonstrate that high Mg levels potentiate cell proliferation and inhibit osteogenic differentiation of bMSCs [72,73,74]. It is worthwhile to note that Mg 2 ATP species form at intra-cellular Mg concentration >5 mM to the detriment of MgATP 2− [9], the latter being the biological active species required for enzyme activity and, hence, cellular function.…”
Section: Discussionmentioning
confidence: 99%
“…Contrasting results were reported in the literature about the Mg effect on bMSC fate. Some studies on the effect of Mg alloy degradation show cell mineralization induction [70,71], while most of the studies demonstrate that high Mg levels potentiate cell proliferation and inhibit osteogenic differentiation of bMSCs [72,73,74]. It is worthwhile to note that Mg 2 ATP species form at intra-cellular Mg concentration >5 mM to the detriment of MgATP 2− [9], the latter being the biological active species required for enzyme activity and, hence, cellular function.…”
Section: Discussionmentioning
confidence: 99%
“…FAK in integrin signal integration can directly activate ERK signaling and promote osteogenic gene expression. Berglund et al (2017) . Effects of novel Mg-Ca-Sr alloys on cellular mechanisms during degradation ion concentrations of alloy degradation products were found to be specific to hMSCs had a dual effect, increasing cell proliferation and possibly inducing osteogenesis, the effect on proliferation was attributed to the presence of Sr, whereas the addition of Mg appeared to induce osteogenesis.…”
Section: Mechanisms Of Osteogenesis Of Mg Matrix Compositesmentioning
confidence: 99%
“…These are known to be suitable for use in clinical stem cell therapy. [58,59] Berglund et al [60] have recently reported that Mg-Ca-Sr alloys have advantageous properties such as adequate mechanical strength, degrading activity, and biocompatibility. Yu et al…”
Section: Mscs and Bone Biomaterials Interactionsmentioning
confidence: 99%